2017
DOI: 10.1111/ejss.12429
|View full text |Cite
|
Sign up to set email alerts
|

Extreme effects of drought on composition of the soil bacterial community and decomposition of plant tissue

Abstract: Summary The decomposition of soil organic matter, as an essential part of nutrient cycling, has a crucial role in maintaining soil fertility and the regulation of climate. This function of the soil is likely to be affected by extreme weather events that are expected to be more frequent and severe in the future. We conducted an experiment from March 2014 to March 2015 to test the effects of extreme drought on composition of the bacterial community and decomposition of plant tissue with soil microclimate variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 36 publications
(47 reference statements)
9
37
0
1
Order By: Relevance
“…In both OJ and LP we found that shade stress had little impact on bacterial richness and soil community diversity. This is consistent with other studies showing that community diversity is not significantly impacted by drought [32,33]. Similar results have been reported in salt stress, demonstrating that increasing salinity has no effect on total bacterial community richness [34].…”
Section: Plant Shade Tolerance Is Related To Bacterial Community Compsupporting
confidence: 92%
“…In both OJ and LP we found that shade stress had little impact on bacterial richness and soil community diversity. This is consistent with other studies showing that community diversity is not significantly impacted by drought [32,33]. Similar results have been reported in salt stress, demonstrating that increasing salinity has no effect on total bacterial community richness [34].…”
Section: Plant Shade Tolerance Is Related To Bacterial Community Compsupporting
confidence: 92%
“…In both OJ and LP, we found that shade stress had little impact on bacterial richness and soil community diversity. This is consistent with other studies showing that community diversity is not significantly impacted by drought [24,25]. Similar results have been reported in salt stress demonstrating that increasing salinity has no effect on total bacterial community richness [26].…”
Section: Plant Shade Tolerance Is Related To Bacterial Community Compsupporting
confidence: 92%
“…Plants and their root-associated microbial communities are strongly interlinked, as a result, perturbations in the abiotic stress directly or indirectly influence plants, their associated microbial communities as well as the interaction between these organisms [8] . In both OJ and LP, we found that shade stress had little impact on bacterial richness and soil community diversity, which is consistent with other studies showing that community diversity is not significantly impacted by drought [14,15].…”
Section: Plant Shade Tolerance Is Related To Bacterial Community Compsupporting
confidence: 92%